The art of aging well: a study of the relationship between recreational arts engagement, general health and mental wellbeing in cohort of Australian older adults - Davies, Christina R.; Budgeon, Charley A.; Murray, Kevin; Hunter, Michael; Knuiman, Matthew (Frontiers in Public Health, 2023)
Introduction: Evidence of the benefits of arts engagement to community wellbeing has been mounting since the 1990s. However, large scale, quantitative, epidemiological studies of the ‘arts–healthy ageing’ relationship, or the types of arts older adults voluntarily choose to engage in as part of their everyday life, for enjoyment, entertainment or as a hobby (versus therapy or intervention) are limited. The aims of this study were to describe older adult recreational arts engagement via the Busselton Healthy Ageing Study cohort, and determine if there was an association between arts engagement, general health and mental wellbeing. Methods: Overall, 2843 older adults (born 1946-1964) from the BHAS cohort (n=5107) who had completed a supplementary arts survey (n=3055, 60%) and had data on required variables were included in this study (93% of those eligible). The dependent variable was general health (SF12) and subjective mental well-being (Warwick-Edinburgh Mental Well-being Scale, WEMWBS). The independent variable was hours engaged in recreational arts in the last 12 months. A descriptive analysis followed by a linear regression analysis was conducted. Results: The prevalence of recreational arts engagement in the last 12 months was 85% (mean=132hrs/year). Older adults engaged in the arts in a number of ways including attending events (79%), actively participating/making art (40%), as an arts society/club/organisation member (20%), by learning about the arts (13%) or by volunteering/working in the arts (non-professional, 11%). When general health was assessed via the SF12, the average physical component score (PCS) was 50.1 (SD 8.9) and the average mental component score (MCS) was 53.6 (SD 8.3). When mental wellbeing was assessed, the average WEMWBS score was 54.9 (SD=8.6). After adjustment for demographic and lifestyle covariates, it was found that older adults who engaged in any recreational arts in the last 12 months had significantly higher WEMWBS scores and higher SF12 physical component scores than those who did not engage in the arts (0 hours/year). Discussion: Evidence of an arts-health relationship was found in this study. The suitability of the arts as a population based, healthy ageing strategy to influence the mental well-being and general health of older adults should be investigated further.